HARMONISASI UNDANG-UNDANG NOMOR 10 TAHUN 2009 TENTANG KEPARIWISATAAN DENGAN PRAKTIK PERDAGANGAN INTERNASIONAL DI BIDANG JASA PARIWISATA DI INDONESIA - , Muslim Aziz, SH, Aminoto, S.H., M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Indonesia has big potency in tourism. This, is admitted not only by our tourist observers but also by other parties abroad. While tourism is being developed at the same time we face liberalization on trade in services. And tourism is one of the sector entered in to liberalization. This research combines both library and field research. Law number 10/2009 and GATS-WTO completed with other literatures become pure legal premise, proceeded with field research. Field research is needed to see not only law in concretto, but also what ideal is. Globalization/liberalization with their regulations gives opportunities and challenges at the same time. And liberalization in a country where massive agrarian remain and rural area scatters are something not easy, moreover trade liberalization in services i.e. tourism. Law no. 9/2009 is to respond the above mentioned liberalization. The law is effective and become a base of tourist activities and shall be able to perform its usefulness. Indonesia is rich in natural wealth with its potency for tourism, this should be transformed in to enactment of a law. Law No. 10/2009 vis-a-vis GATS regulations which is part of the three legs of WTOâs liberalization.other legs are GATT and TRIPS. Stipulations which are conformed between two regulations are found, besides there are stipulations which may negotiated in the next future for the sake of justice